Geomorfologia e controle estrutural da rede de drenagem do alto curso do Rio Jaguaribe, Ceará - Silva, Mickaelle Braga da (2017)
This research presents the upper course of Jaguaribe river, Ce, emphasizing its geomorphological aspects. This study aimed to analyze the influence that geological structure presents in the drainage network of the area with the utilization of remote sensing products and geoprocessing techniques. Thus, it became necessary to pursue some stages, they were: bibliographical and cartographic surveys; Geoprocessing techniques application, tabulation e data analysis. Among the remote sensing products available for the area, stands out the Shuttle Radar Topography Mission-SRTM data, with 30 meters of resolution. These products with the geoprocessing software aid allowed the extraction of the drainage network and relief lineaments; Identification and delimitation of morphostructural units; Morphostructural compartmentalization of lineaments; Identification and distribution of drainage patterns. It was also used the statistics application and rosette graphic generation in the spatialization of the preferred direction of drainage frequency and the relief lineaments. In this context, it was possible to identify drainage patterns controlled by structures (trellis and parallel patterns). The data demonstrated a significant compatibility of NE-SW and E-W directions, which suggest positive and negative relief lineaments represented by ridges and valleys and craggy rectilinear sections, confining drainage channels. Thus, it was possible to establish links with the distribution of lineament density and drainage patterns, noting that, in tectonically sectors with more deformation, there is the highest concentration of controlled structurally channels. In order to identify and quantify possible anomalies in the drainage network of the area, were applied the morphometric indexes related to the longitudinal profile and the Stream-Length Gradient Index (SL). The indexes allowed relating channels in their total extensions and by stretches with factors related to the rocky substratum and geological structure. The indexes application and the identification of anomalous stretches presented four main responses to the drainage network of the area. Standing out the occurrence of stretches with influence of variables such as lithological control; Structural control; river channels confluence and according the elimination of the mentioned factors, it was identified a significant concentration of anomalies in cretaceous terrains of the Araripe sedimentary basin that suggest an investigation of the occurrence of neotectonic events in the area.